Notary Responsibility for Loss of Land Title Due to Notary Negligence - Risko Fitriano; Jeane Neltje Saly (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This article discusses the notary's responsibility for the loss of land certificates due to the notary's negligence. This research uses normative or literature research methods by analyzing relevant laws and regulations regarding the authority and responsibilities of notaries. The research results show that notaries have civil liability for losses caused by negligence or deliberate action in carrying out their duties. This civil liability includes reimbursement of costs, compensation and interest to the party who feels aggrieved. Notaries also have a professional code of ethics that regulates their duties and responsibilities, including the obligation to safeguard the interests of related parties and act with integrity. In the case of loss of a land title certificate, the notary must be responsible for the documents entrusted and may be subject to civil sanctions if negligence occurs.